2022
DOI: 10.23818/limn.41.16
|View full text |Cite
|
Sign up to set email alerts
|

Seston and eutrophication on a tropical karst lake district: Lagunas de Montebello, Chiapas, Mexico

Abstract: Large quantities of seston are among the most important indicators of eutrophication in aquatic ecosystems. The present study aimed to elucidate the role seston plays in the general limnological dynamics of a cluster of eighteen tropical karstic lakes with different anthropic impacts (non-impacted, oligotrophic, clear-water lakes, and impacted, eutrophic, turbid-water lakes) of the “Lagunas de Montebello” National Park lake district. The seston concentration was measured twice, in the warm/rainy and the cold/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…DCM are characteristic features of oligotrophic waters ( Cullen, 1982 ; Fee, 1976 ). Although research in other study sites has shown that eutrophication increases towards the summer when stratification reaches its maximum, Vargas-Sánchez, Alcocer & Oseguera (2022) found higher Chl-a concentrations in the lakes of the LMNP during the cold/dry season (winter) than in the warm/rainy season (summer). Tropical warm monomictic lakes show characteristic winter phytoplankton blooms associated with the full water column mixing ( Lewis Jr, 1996 ; Sarmento, 2012 ).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…DCM are characteristic features of oligotrophic waters ( Cullen, 1982 ; Fee, 1976 ). Although research in other study sites has shown that eutrophication increases towards the summer when stratification reaches its maximum, Vargas-Sánchez, Alcocer & Oseguera (2022) found higher Chl-a concentrations in the lakes of the LMNP during the cold/dry season (winter) than in the warm/rainy season (summer). Tropical warm monomictic lakes show characteristic winter phytoplankton blooms associated with the full water column mixing ( Lewis Jr, 1996 ; Sarmento, 2012 ).…”
Section: Discussioncontrasting
confidence: 56%
“…Esmeralda is a “functionally shallow” (warm polymictic) lake, while the other 11 lakes are deep, warm, and monomictic ( Cortés-Guzmán, Alcocer & Oseguera, 2019 ). The trophic classification was designated according to Vargas-Sánchez, Alcocer & Oseguera (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…The T and DO vertical profiles during the stratification season showed major differences between non-impacted/oligotrophic and impacted/eutrophic lakes despite similar average values. [53] reported shallower (5.3 ± 1.5 m) thermoclines with stronger (0.8 ± 0.2 • C m −1 ) thermal gradients in impacted/eutrophic lakes, comparing with deeper (14.0 ± 7.1 m) and weaker (0.5 ± 0.1 • C m −1 ) thermal gradients in non-impacted/oligotrophic. All lakes' hypolimnia became anoxic and uninhabitable for aerobic organisms during the stratification.…”
Section: Discussionmentioning
confidence: 88%
“…The anthropogenic impacts supplying agricultural fertilizers and urban wastewater to the lakes since the early 1950s drove the lakes' eutrophication [25,54]. Some authors [24,53] reported high nutrient, Chl-a, seston, and particulate organic carbon concentrations in the impacted/eutrophic lakes. The nuisance cyanobacterial scums in some of the PNLM lakes ratified the advanced state of eutrophication, which negatively impacts tourism and the general economic development of the area [55].…”
Section: Discussionmentioning
confidence: 99%
“…The "Lagunas de Montebello" National Park (LMNP), located in Chiapas State, extends over one of Mexico's main karst lake districts. The LMNP has more than 130 karst water bodies of different morphometric and physicochemical characteristics [33][34][35]. Since these lakes can be found throughout gradients related to groundwater and surface water inputs, contaminated effluents, surrounded by agriculture or pristine forests, provide a unique opportunity to assess CO 2 emissions mechanisms together with eutrophication effects, considering a wide variety of lakes.…”
Section: Introductionmentioning
confidence: 99%